Impacts of Africa RISING in Mali - Haile, Beliyou; Azzarri, Carlo; Boukaka, Sedi Anne; Tzintzun, Ivan; Vitellozzi, Sveva (International Food Policy Research Institute, 2024)
This study evaluates the impact of Africa RISING, a sustainable intensification (SI) program, implemented in Bougouni, Yanfolila, and Koutiala cercles in southern Mali beginning in 2012. Using a participatory action research framework, the program validated and promoted alternative SI options including fertilized groundnut and sorghum, crop-legume intercropping, intercropping of two compatible legumes, access to extension services, and fertilizer microdosing, while preserving ecosystem services in the face of projected population growth and climatic changes. Impact is estimated on several SI indicators and domains using two rounds of quasi-experimental panel data (surveys conducted in 2014 and 2022) and difference-in-differences techniques. The unique study design allows us to estimate the impact of Africa RISING by comparing outcomes among program beneficiaries with two different counterfactual groups—one located inside program villages (within-village comparison) and another in non-program (control) villages (out-of-village comparison) on several indicators across five SI domains—environment, productivity, economic, human, and social. We also conduct a placebo test comparing non-beneficiaries in the two counterfactual groups. We find few statistically significant differences in the averages of the characteristics in the environmental and productivity domain among households in the within-village and out-of-village comparisons, most likely because of misreporting of program participation. Overall comparisons between households in target and non-target villages show a positive impact of AR on environmental variables such as access to extension services, and adoption of improved crops; on productivity variables such as green bean, cotton and okra yield; and on economic variables such as an increase in the non-agricultural wealth index; but no statistically significant effect on human and social indicators, namely household dietary diversity, food consumption scores, and nutritional indicators for children 0–59 months old and women 15–49 years old. Estimates based on within-village, out-of-village, and placebo comparisons suggest important insights about the challenges in assessing the impact of agricultural programs in general and, specifically, participatory multi-intervention programs in the presence of sample (self-)selection and spillovers. Our study highlights useful empirical lessons learned to inform future program design and impact assessments.